PENGARUH MODEL PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) TERHADAP PEMAHAMAN KONSEP IPA, KETERAMPILAN PROSES SAINS DAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP NEGERI 3 PRINGGABAYA LOMBOK TIMUR - Rustam -; Agus Ramdani; Prapti Sedijani (Jurnal Penelitian Pendidikan IPA, 2017)
This research is aimed at determining the effect of POGIL model teaching on the understanding of Natural Science Concept, Skill of Sciences Process, and Critical Thinking Capability of student in photosynthesis. This research is a experiment with nonequivalent control group design. The sample were selected randomly and the hypothesis was analized with Manova and t-test. The rsearch concludes that (1) there an effect of POGIL model teaching in understanding Natural Sciences concept (2) there an effect of POGIL model teaching on Skill of Sciences Process (3) there an effect of POGIL model teaching on the capability of critical thinking (4) there is simultaneous effect of the application of POGIL model teaching on the Natural Sciences concept, Skill of Sciences Process and in the capability of critical thinking.Keywords: POGIL, understanding Natural Sciences concept, Skill of Sciences Process and the capability of critical thinking